Perubahan Sosial Ekonomi Masyarakat Kecamatan Belitang Kabupaten Ogan Komering Ulu Timur (2004-2013) - Yunani Yunani; Efriyandika Hadi (Criksetra: Jurnal Pendidikan Sejarah, 2017)
Abstract The problem raised in this research is how the socio-economic changes of Belitang District of East Ogan Komering Ulu in 2004-2013. This study uses historical research methods, a systematic framework to collect historical sources, by giving criticism and judgment in selecting facts, to obtain the truth and present it in writing and to interpret and analyze the data. The social aspects observed in this study include institutions and institutions such as government agencies, religious institutions, educational institutions, health institutions and the population. While the observed economic aspects include agriculture, plantation, animal husbandry and fisheries. Socio-economic changes in Belitang society are influenced by government servants to maximize society and society's insight into the importance of education and health, and the increasing number of migrant population. The development in the economic aspect in the form of increasing livelihood and increasing facilities and knowledge in farming and raising.